A New Species of Dendrostoma (Erythrogloeaceae, Diaporthales) Identified by Combined Morphological and Phylogenetic Studies - Ding, Peng-Cheng; Madhushan, Asanka; Shami, Ashwag; Alharbi, Nada K.; Liu, Jian-Kui; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2025)
Dendrostoma is a genus of plant pathogens known to be associated with canker diseases. During our ongoing study of fungal diversity in Sichuan Province, China, we isolated an unidentified fungus from the decaying branches of an unknown host. Based on the preliminary BLAST results of the internal transcribed spacer (ITS) region, the isolate was identified as belonging to the genus Dendrostoma. To clarify its phylogenetic position, we conducted combined analyses using sequence data from the ITS, large subunit ribosomal RNA (LSU), the second largest subunit of RNA polymerase II (rpb2), and partial translation elongation factor-1 alpha (tef1-α) regions. Phylogenetic analysis indicated that our isolate constitutes a distinct lineage closely related to D. rizhaoense and D. castanopsidis, yet clearly separated as an independent branch. Morphologically, the new species differs from D. rizhaoense in having slender conidiogenous cells and more regularly shaped conidia with numerous small, drop-like spots, compared to the shorter, broader, and more variable conidia of D. rizhaoense. Compared to D. castanopsidis, the new species has longer conidiogenous cells and conidia, which are ellipsoid to fusoid rather than cylindrical to clavate and biguttulate. Therefore, based on the phylogenetic evidence and morphological distinctions, we introduce this new taxon as Dendrostoma multiguttulum.